Support for and willingness to be involved in voluntary assisted dying: a multisite, cross‐sectional survey study of clinicians in Victoria, Australia. Issue 10 (18th October 2021) - Sellars, Marcus; Tacey, Mark; McDougall, Rosalind; Hayes, Barbara; Pratt, Bridget; Hempton, Courtney; Detering, Karen; Aldrich, Rosemary; Benson, Melanie; Kirwan, Jeffrey; Gold, Michelle; O'Driscoll, Lisa; et al.
Abstract: Background: In the Australian state of Victoria, specialist doctors are central to the operation of voluntary assisted dying (VAD). However, a broad range of clinicians may be involved in the care of patients requesting or using VAD. Aims: To describe levels of support for and willingness to be involved in VAD and consider factors associated with clinician support for the VAD legislation and physicians' willingness to provide VAD in practice. Methods: A multisite, cross‐sectional survey of clinicians in seven Victorian hospitals. All clinicians were invited to complete an online survey measuring demographic characteristics, awareness of and support for the VAD legislation, willingness to participate in VAD related activities and reasons for willingness or unwillingness to participate in VAD. Results: Of 5690 who opened the survey, 5159 (90.1%) were included in the final sample and 73% ( n = 3768) supported the VAD legislation. The strongest predictor of support for the VAD legislation was clinical role. Forty percent ( n = 238) of medical specialists indicated they would be willing to participate in either the VAD consulting or coordinating role. Doctors did not differ in willingness between high impact (44%) and low impact specialty (41%); however, doctors specialising in palliative care or geriatric medicine were significantly less willing to participate (27%). Conclusion: Approximately 73% of surveyed staff supported Victoria's VAD legislation. However, only a minority of medical specialists reported willingness to participate in VAD, suggesting potential access issues for patients requesting VAD in accordance with the legal requirements in Victoria.